2009
DOI: 10.1001/jama.2009.761
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Tempo of First-Year Rapid Growth in Relation to Cardiovascular and Metabolic Risk Profile in Early Adulthood

Abstract: ContextGrowth during infancy appears to be an important determinant of cardiovascular disease and type 2 diabetes later in life.Objectives To specify which period in the first year of life is related to determinants of cardiovascular disease and type 2 diabetes in early adulthood and to investigate the association between tempo of first-year weight gain (Ͼ0.67 SDs) and these determinants.Design, Setting, and Participants Observational study using longitudinal data collected in the Programming Factors for Growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
365
4
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(400 citation statements)
references
References 34 publications
16
365
4
8
Order By: Relevance
“…96 Consistent with this finding is the observation that fast weight gain in the first 3 months of life is inversely associated with insulin sensitivity and serum high-density lipoprotein cholesterol level, whereas is positively associated with waist circumference, acute insulin response, ratio of total cholesterol to high-density lipoprotein cholesterol and level of triglycerides in early adulthood. 107 Finally, a large study on adults with coronary events showed that the association of low-birth weight and rapid weight gain after the age of 2 years was associated with insulin resistance and risk of coronary events in later life. 108 These findings could be explained by the fact that infants who have experienced intrauterine growth Figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…96 Consistent with this finding is the observation that fast weight gain in the first 3 months of life is inversely associated with insulin sensitivity and serum high-density lipoprotein cholesterol level, whereas is positively associated with waist circumference, acute insulin response, ratio of total cholesterol to high-density lipoprotein cholesterol and level of triglycerides in early adulthood. 107 Finally, a large study on adults with coronary events showed that the association of low-birth weight and rapid weight gain after the age of 2 years was associated with insulin resistance and risk of coronary events in later life. 108 These findings could be explained by the fact that infants who have experienced intrauterine growth Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the early exposure to high nutrient intake and rapid weight gain in infancy are associated with metabolic risk in adolescence and adulthood. 96,107,113 Innovative feeding strategies should be finely balanced to guarantee appropriate brain development and catch-up growth, without exposing the infant to postnatal nutritional programming. 113 Future research will test the feasibility and effectiveness of targeted nutritional interventions at different stages of development (from periconceptual time to puberty) in preventing or reversing the epigenetic programming.…”
Section: Towards Targeted Interventionsmentioning
confidence: 99%
“…Rapid early infant weight gain predisposes to an adverse metabolic phenotype in later life, with increased risk of overweight 2, central adiposity and insulin resistance 3. The type of infant milk feeding (exclusive breast feeding, formula feeding or mixing feeding), as well as specific dietary compositions and volume of intake, may be important factors.…”
Section: Introductionmentioning
confidence: 99%
“…childhood 33,34 and in adolescence 35 and for several determinants of cardiovascular disease and type 2 diabetes in early adulthood. 36 Further studies are required to investigate whether and when a critical window during which infant weight gain programs later health exists.…”
Section: Discussionmentioning
confidence: 99%